The LRRC8A Mediated “Swell Activated” Chloride Conductance Is Dispensable for Vacuolar Homeostasis in Neutrophils - Philippe Behe; Juliet R. Foote; Adam P. Levine; Craig D. Platt; Janet Chou; Fernando Benavides; Raif S. Geha; Anthony W. Segal (Frontiers in Pharmacology, 2017)
The dialysis of human and mouse neutrophils in patch clamp experiments in the conventional whole-cell mode induces the emergence of a chloride (Cl-) current that appeared to be primarily regulated by cytoplasmic ionic strength. The characteristics of this current resembled that of the classical, and ubiquitous volume-sensitive outwardly rectifying Cl- current: strong outward rectification, selectivity sequence of the Eisenman1 type, insensitivity to external pH and strong inhibition by tamoxifen, DCPIB and WW781. We show that this current is essentially supported by the leucine rich repeat containing 8 A (LRRC8A); the naturally occurring LRRC8A truncation mutant in ebo/ebo mice drastically reduced Cl- conductance in neutrophils. Remarkably, the residual component presents a distinct pharmacology, but appears equally potentiated by reduced ionic strength. We have investigated the role of the LRRC8A-supported current in the ionic homeostasis of the phagosomal compartment. The vacuolar pH, measured using SNARF-1 labeled Candida albicans, normally rises because of NADPH oxidase activity, and this elevation is blocked by certain Cl- channel inhibitors. However, the pH rise remains intact in neutrophils from the ebo/ebo mice which also demonstrate preserved phagocytic and respiratory burst capacities and normal-sized vacuoles. Thus, the LRRC8A-dependent conductance of neutrophils largely accounts for their “swell activated” Cl- current, but is not required for homeostasis of the phagosomal killing compartment.